2010
DOI: 10.1161/strokeaha.109.575993
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Neural Stem Cells After Intravascular Therapy for Hypoxic–Ischemia

Abstract: Background and Purpose Intravascular transplantation of neural stem cells represents a minimally invasive therapeutic approach for the treatment of central nervous system diseases. The cellular biodistribution after intravascular injection needs to be analyzed to determine the ideal delivery modality. We studied the biodistribution and efficiency of targeted central nervous system delivery comparing intravenous and intra-arterial (IA) administration of neural stem cells after brain ischemia. Methods Mouse ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 34 publications
(32 reference statements)
6
137
0
1
Order By: Relevance
“…136 Furthermore, efficacy of treatment may also depend on the administration route. Recently, it has been shown that intravenously injected mononuclear cells 137 and NSCs 138 are not only detected in the brain, but also in a substantial amount in the spleen, 137 and liver and lungs, respectively. 138 Hence, significantly less of the injected stem cells will end up in the brain after intravenous delivery as they will circulate throughout the body and may even have an undesired effect in other organs.…”
Section: Stem-cell Based Therapy: Enhancing the Neurogenic Potentialmentioning
confidence: 99%
“…136 Furthermore, efficacy of treatment may also depend on the administration route. Recently, it has been shown that intravenously injected mononuclear cells 137 and NSCs 138 are not only detected in the brain, but also in a substantial amount in the spleen, 137 and liver and lungs, respectively. 138 Hence, significantly less of the injected stem cells will end up in the brain after intravenous delivery as they will circulate throughout the body and may even have an undesired effect in other organs.…”
Section: Stem-cell Based Therapy: Enhancing the Neurogenic Potentialmentioning
confidence: 99%
“…Least effective method is mobilization from peripheral blood or bone marrow (170)(171) and most effective method is intracoronary infusion (172)(173). And in case of intravenous infusion, according to the blood flow, all blood in body has to pass the lung and some proportion of infused stem cells are trapped at the lung (174)(175). Some are trapped at other organs (176).…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not been supported by other studies on the biodistribution of NSCs following intravenous administration. 44 Finally, Franchi et al's study results are restricted to the chronic constriction injury model of peripheral neuropathic pain and cannot be extrapolated to other neuropathic pain models.…”
Section: Evidence On the Utility Of Adult Stem Cells For The Treatmenmentioning
confidence: 96%